An Investigation of Teaching English at Bintang Nusantara Learning Centres in Hong Kong: Instructional Method, Problems and Solutions - Ana Dwi Ratnawati; Andang Saehu; Udan Kusmawan (Institut Agama Islam Negeri Palopo, 2024)
This study reported the implementation of synchronous and asynchronous classes at Bintang Nusantara Learning Centre, focusing on the use of the Communicative Language Teaching (CLT) method to develop students' speaking skills. This research was conducted as a case study, employing qualitative methods such as observations, interviews, and document analysis to gather in-depth data on the teaching and learning processes. The learning process was structured into three interconnected stages: pre-teaching, whilst teaching, and post-teaching, with each stage encompassing various activities designed to enhance student engagement and language proficiency. Despite the careful planning and execution of these activities, both teachers and students faced a range of technical and non-technical challenges throughout the learning process in both online and offline settings. Technical issues included unstable internet connections, inadequate devices (software and hardware), and varying levels of technological proficiency among both teachers and students , which disrupted the flow of online classes. Non-technical challenges involved a lack of motivation and engagement from students, as well as difficulties in replicating the interactive nature of CLT in a virtual environment. However, teachers and students collaborated to find solutions, such as employing alternative communication tools, adjusting lesson plans to better suit the online format, and providing additional support and encouragement to maintain student motivation. In offline classes, issues related to health protocols and classroom management were addressed by implementing smaller class sizes and ensuring compliance with safety measures. These efforts were critical in mitigating the impact of the challenges, allowing the teaching methodology to remain effective in both online and offline contexts.